Growth and yield of over-aged rice (Oryza sativa) seedlings under different nitrogen levels in waterlogged situations - CHOWDHURY, S ROY; BRAHMANAND, P S; KUMAR, ASHWANI; KUNDU, D K; BEHERA, M S (The Indian Journal of Agricultural Sciences, 2026)
Seedlings of three different ages, ie 30, 45 and 60 days old of rice were grown at three different N levels, ie 0, 20 and 40 kg/ ha, for two years in waterlogged condition. Eventhough panicle number showed marginal increase, the panicle growth was superior in older seedlings more so at higher nitrogen level. The panicle length, spikelet number/panicle, panicle weight and number of filled grains/panicle showed significant improvement in older seedlings than younger seedlings of 30 days old. The effect was more pronounced at higher N level. The harvest index was also better in older seedlings at higher N level. In both the years 2007 and 2008 respectively the yield showed closer association with harvest index (r2 = 0.52, 0.76; n 27) than with total dry matter produced (r2 = 0.21, 0.56; n 27) suggesting importance of dry matter partitioning efficiency than total dry matter production efficiency for improvement of yield in waterlogged areas.